Correlation between koilocytes and human papillomavirus detection by PCR in oral and oropharynx squamous cell carcinoma biopsies - Miyahara, Glauco Issamu [UNESP]; Simonato, Luciana Estevam [UNESP]; Mattar, Neivio José [UNESP]; Camilo Jr, Deolino João [UNESP]; Biasoli, Eder Ricardo [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2011)
The purpose of this study was to compare the histopathological analysis with polymerase chain reaction (PCR) methods to predict the presence of human papillomavirus (HPV) infection in oral squamous cell carcinoma biopsies. Eighty-three paraffin-embedded tissue specimens from patients with oropharynx and mouth floor squamous cell carcinoma were submitted to histopathological analysis under light microscopy, specifically for the determination of the presence of koilocytes. Subsequently, DNA was purified from the same paraffin-embedded specimens and submitted to PCR. Fisher's exact test showed no statistically significant correlation between the two methods. The results suggest that the presence of koilocytes is unreliable for the detection of HPV presence in oral and oropharynx squamous cell carcinoma.
Keywords: human papillomavirus; squamous cell carcinoma; microscopy; polymerase chain reaction